Repair bond strength of a resin composite to alumina-reinforced feldspathic ceramic - Goia, Tamiye Simone [UNESP]; Leite, Fabíola Pessôa Pereira [UNESP]; Valandro, Luiz Felipe [UNESP]; Özcan, Mutlu; Bottino, Marco Antonio [UNESP] (My University, 2006)
This study compared the microtensile bond strength of a repair resin to an alumina-reinforced feldspathic ceramic (Vitadur-α, Vita) after 3 surface conditioning methods: Group 1, etching with 9.6% hydrofluoric acid for 1 minute plus rinsing and drying, followed by application of silane for 5 minutes; group 2, airborne particle abrasion with 110-mm aluminum oxide using a chairside air-abrasion device followed by silane application for 5 minutes; group 3, chairside tribochemical silica coating with 30-μm SiOx followed by silane application for 5 minutes (N = 30). Group 1 presented the highest mean bond strength (19.7 ± 3.8 MPa), which was significantly higher than those of groups 2 (10 ± 2.6 MPa) and 3 (10.4 ± 4 MPa) (P < .01). Scanning electron microscope analysis of the failure modes demonstrated predominantly mixed types of failures, with adhesive and/or cohesive failures in all experimental groups.